FORM AND CONTENT UPDATE AND RESEARCH IN CHILDREN'S POETRY (Scientific journal of the Fergana State University, 2025)
The article talks about the place of children's literature in Uzbek literature and the research of form in children's poetry. Humorous poetry should not be understood only as light poetry that makes people laugh and makes people smile. Especially if it is written for children, certain tasks should be assigned to the comic. In recent years, the term "shallow" has been applied to the concepts of children's literature and children's reading, and it may be because these tasks have not been fulfilled.